Therapeutic effect of bovine amniotic fluid in murine dry eye model - Kulualp, Kadri; Kilic, Servet; Eroksuz, Yesari; Eroksuz, Hatice; Aslan, Abdullah (Hokkaido Univ, 2020)
This study investigated the therapeutic effect of bovine amniotic fluid (BAF) in dry eye (DE) model in 60 female BALB/c mice divided equally into 6 groups. Control group (CG) received 5 mu L formal saline and experimental groups 0.2% benzalkonium chloride in both eyes twice a day during 14 days. From 15 to 30 days while CG and DE group only was administered saline, other groups called BAF20, BAF35, BAF50 and BAF100 received 5 mu L 20, 35, 50 and 100% BAF three times a day, respectively. On day 15, in all experimental groups tear production decreased, tear break-up time shortened, corneal fluorescein staining score increased compared to baseline; on day 30, for these parameters the most effective BAF concentrations were 35%, 50% and 100%. According to western blot analysis the lowest levels were obtained in CG and BAF35 groups for tumor necrosis factora (TNF-alpha), vascular endothelial growth factor (VEGF) and cytokeratin 10 (K10); CG for adiponectin receptor-1 (AdipoR1); BAF35 and CG for adiponectin receptor-2 (AdipoR2) (P < 0.05). In the immunohistochemical analysis the lowest levels were in CG, BAF35, BAF50 and BAF100 groups for TNF-alpha, VEGF and K10; CG, BAF35 and BAF50 groups for AdipoR1; CG, BAF20, BAF35 and BAF50 groups for AdipoR2 (P < 0.05). TUNEL method revealed a lower apoptotic cell score in all BAF groups (P > 0.05). In conclusion; moderate to high concentrations of BAF have the more beneficial effects on DE at molecular and clinical signs and it can be used for the treatment.
Keywords: bovine amniotic fluid; dry eye; inflammation; mice; treatment